2020
DOI: 10.1111/sms.13821
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral effects of eccentric resistance training on immobilized arm

Abstract: This study compared the effects of contralateral eccentric‐only (ECC) and concentric‐/eccentric‐coupled resistance training (CON‐ECC) of the elbow flexors on immobilized arm. Thirty healthy participants (18‐34 y) were randomly allocated to immobilization only (CTRL; n = 10), immobilization and ECC (n = 10), or immobilization and CON‐ECC group (n = 10). The non‐dominant arms of all participants were immobilized (8 h·day−1) for 4 weeks, during which ECC and CON‐ECC were performed by the dominant (non‐immobilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 37 publications
1
46
1
1
Order By: Relevance
“…The greater increase in the strength in the study by Tseng et al (2020) may be due to the focus on eccentric contractions. Valdes et al (2021) reported that elbow flexor eccentric-only resistance training performed by the dominant (non-immobilized) arm 3 times a week with 80–120% of one concentric 1-RM load increased MVC-ISO strength (20.9%) greater than concentric-eccentric coupled resistance training (13.7%) in which 60–90% of 1-RM load was used for the same total training volume. It seems possible that eccentric-only resistance training is more effective for increasing muscle strength.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The greater increase in the strength in the study by Tseng et al (2020) may be due to the focus on eccentric contractions. Valdes et al (2021) reported that elbow flexor eccentric-only resistance training performed by the dominant (non-immobilized) arm 3 times a week with 80–120% of one concentric 1-RM load increased MVC-ISO strength (20.9%) greater than concentric-eccentric coupled resistance training (13.7%) in which 60–90% of 1-RM load was used for the same total training volume. It seems possible that eccentric-only resistance training is more effective for increasing muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of increase in the other muscle strength measures was probably due to the low intensity of training in the first half of the training period (1–3 sessions) and the lower training volume, as mentioned above. The factors that influence the magnitude of the cross-education effect include training intensity ( Colomer-Poveda et al, 2020 ), muscle contraction type ( Hortobagyi et al, 1997 ; Kidgell et al, 2015 ; Manca et al, 2017 ; Tseng et al, 2020 ; Valdes et al, 2021 ), number of sessions ( Barss et al, 2018 ), and intervention duration ( Manca et al, 2021 ). Some studies have reported that the cross-education effect is greater after eccentric than concentric resistance training ( Hortobagyi et al, 1997 ; Kidgell et al, 2015 ; Tseng et al, 2020 ) or concentric-eccentric coupled training ( Valdes et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggest that ET increased MVIC torque of the trained and non-trained arms more similarly than CT. Previous studies have reported a greater cross-education effect on MVIC strength after ET than CT [ 20 , 22 , 31 , 32 ]. For example, Kidgell et al [ 22 ] reported that after 4 weeks of unilateral resistance training of the wrist flexors performed three times a week, the increase in MVIC strength was greater in ET (43 %) than CT (11 %) for the non-trained arm.…”
Section: Discussionmentioning
confidence: 99%